Determining the Different Mechanisms Used by Pseudomonas Species to Cope With Minimal Inhibitory Concentrations of Zinc via Comparative Transcriptomic Analyses - Lei, Lei; Chen, Jiahui; Liao, Weifang; Liu, Pulin (Frontiers in Microbiology, 2020)
Pseudomonas is one of the most diverse bacterial genera identified in the environment. Genome sequence analysis has indicated that this genus can be clustered into three lineages and ten groups. Each group can adopt different mechanisms to thrive under zinc-depleted or high-zinc conditions, two environments that are frequently encountered during their environmental propagation. The response of three prominent Pseudomonas strains (Pseudomonas aeruginosa PAO1, Pseudomonas putida KT2440, and Pseudomonas fluorescens ATCC 13525T) to minimal inhibitory concentrations of zinc were compared using RNA-seq and ultra-performance liquid chromatography–tandem mass spectrometry analysis. Results demonstrated that the three strains shared only minimal similarity at the transcriptional level. Only four genes responsible for zinc efflux were commonly upregulated. P. aeruginosa PAO1 specifically downregulated the operons involved in siderophore synthesis and the genes that encode ribosomal protein, while upregulated the genes associated with antibiotic efflux and cell envelope biosynthesis. The membrane transporters in P. putida KT2440 were globally downregulated, indicating changes in cell permeability. Compared with P. aeruginosa PAO1 and P. putida KT2440, the most remarkable transcriptional variation in P. fluorescens ATCC 13525T is the significant downregulation of the type Ⅵ secretion system. Metabolite quantitative analysis showed that low concentrations of the metabolites involved in central carbon metabolism and amino acid synthesis were detected in the three strains. In summary, the cellular responses of the three strains under high-zinc condition is quite divergent. Although similar metal efflux systems were upregulated, the three strains employed different pathways to reduce zinc intrusion. In addition, zinc treatment can increase the difficulties of scavenging P. aeruginosa from its colonisation area, and reduce the competitiveness of P. fluorescens in microbiota.